IMPROVEMENT OF CREATIVE COMPETENCIES OF STUDENTS BY TEACHING THEM TO DRAW ON GRAPHIC MATERIALS IN FINE ARTS CLASSES (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
This article improves students' creative competencies by teaching them to depict graphic materials in fine arts classes. The article includes structural pedagogical strategies of intervention, including step-by-step seminars and project-based learning, which served to develop students' technical skills in graphic materials and increase their ability to solve creative problems. Quantitative data from the preliminary and final assessments conducted using the Torrance Creativity Tests (TTCT) showed significant improvements in fluency, flexibility, originality, and development (p < 0.01). Qualitative data obtained from semi-structural interviews and portfolio analysis noted an increase in students' self-confidence and the use of innovative approaches in the use of materials. This research contributes to the design of higher education curricula on a global scale by proposing a pedagogical model that connects technical skills with creative expression in fine arts education.